Modeling and experimental validation of thin, tightly rolled dielectric elastomer actuators. (19th November 2021) - Prechtl, J; Kunze, J; Moretti, G; Bruch, D; Seelecke, S; Rizzello, G
Abstract: Due to their large deformation, high energy density, and high compliance, dielectric elastomer actuators (DEAs) have found a number of applications in several areas of mechatronics and robotics. Among the many types of DEAs proposed in the literature, rolled DEAs (RDEAs) represent one of the most popular configurations. RDEAs can be effectively used as compact muscle-like actuators for soft robots, since they allow eliminating the need for external motors or compressors while providing at the same time a flexible and lightweight structure with self-sensing capabilities. To effectively design and control complex RDEA-driven systems and robots, accurate and numerically efficient mathematical models need to be developed. In this work, we propose a novel lumped-parameter model for silicone-based, thin and tightly rolled RDEAs. The model is grounded on a free-energy approach, and permits to describe the electro-mechanically coupled response of the transducer with a set of nonlinear ordinary differential equations. After deriving the constitutive relationships, the model is validated by means of an extensive experimental campaign, conducted on three RDEA specimens having different geometries. It is shown how the developed model permits to accurately predict the effects of several parameters (external load, applied voltage, actuator geometry) on the RDEA electro-mechanical response, while maintaining an overall simple mathematical structure.